Skin whitening potential of extracts from discarded cabbage outer leaves - Hamin Lee; Kichan Kim; Kyungtae Park; Bo-Kook Jang; Ju-Sung Cho (Scientific Reports)
Abstract The outer leaves (OL) of Brassica oleracea var. capitata (cabbage) are often discarded as agricultural waste despite their potential health benefits. This study evaluated the skin-whitening, antioxidant, and anti-inflammatory activities of cabbage OL extract (OLE) and compared them with those of cabbage head extract (CHE). OLE exhibited significantly higher levels of total polyphenols, flavonoids, and glucosinolates than did CHE, leading to excellent radical scavenging activities. Additionally, OLE demonstrated strong anti-inflammatory activity by reducing nitric oxide production in RAW 264.7 macrophages. Notably, tyrosinase inhibition activity of OLE reached 100.4% with respect to that of ascorbic acid, a well-known skin-whitening agent. Vitamin C and trace amounts of sulforaphane in OLE, which were absent in CHE, probably contributed to these effects. These findings suggest that cabbage OL, an agricultural byproduct, holds significant promise as a functional ingredient for health products and cosmetics, highlighting its potential for waste valorization.